PENGARUH KERJASAMA PASIAD INDONESIA DENGAN INDONESIA DIBIDANG PENDIDIKAN MENENGAH - Mulyani, Dewi; Nizmi, Yurnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study describes the effect of PASIAD Indonesia cooperation with Indonesia in the field of secondary education. PASIAD Indonesia is a non-governmental organization (NGO) engaged in educational, social, economic and cultural PASIAD Indonesia began working in secondary education in Indonesia since 1995. Until now PASIAD Indonesia has collaborated with 7 private foundations and 3 local governments to hold 10 high school.Perspective that used in this research is Pluralisme perspective. The theory used in this research is International Coorporation dan Transnational Advocacy Network ( TAN). This research used a qualitative method that is an explanatory. by using the techniques of data collection through literature and documentation, ie by collecting data from books, journals, magazines, newspapers, and other sources (document analysis).As a result, the effect of Indonesian PASIAD cooperation with Indonesia in the field of secondary education a positive impact on improving the quality of secondary education in Indonesia. Where PASIAD Indonesia Conducting scientific competition in national and international scale that encourage student creativity thinking and promote the spirit of competition to the students. besides school work partners PASIAD also always present medals to Indonesian state education can improve the image of Indonesia in the international arenaKey words : PASIAD Indonesia, non govermental organization, Transnationa Advocacy Network, secondary education.